Chitosan loaded benzene-containing carboxylic acid nanosheet

By loading α-naphthaleneacetic acid and 3-indole butyric acid on chitosan nanosheets, the problem of limited performance of benzene carboxylic acid in organisms is solved, and the antioxidant and antifungal ability of chitosan is enhanced, and its biocompatibility and application value are improved.

CN119498304APending Publication Date: 2025-02-25INNER MONGOLIA AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411680700.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, benzene carboxylic acids have limited their antioxidant and antifungal properties in organisms due to their good lipid solubility, and most of them use a single substance to conduct antifungal and antioxidant effects experiments, which lacks in-depth biological activity research.

Method used

The free radical scavenging ability and antifungal activity of chitosan is enhanced by loading α-naphthaleneacetic acid and 3-indole butyric acid with antioxidant and antifungal ability onto chitosan nanosheets.

Benefits of technology

It improves the free radical scavenging ability and antifungal activity of chitosan, enhances its biocompatibility and practical application value, and has better effect than traditional antifungal and antioxidants, with less toxic and side effects and lower development costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119498304A_ABST
    Figure CN119498304A_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan-loaded benzene-containing carboxylic acid nanosheet, and relates to the field of nano materials. Alpha-naphthylacetic acid (NAA) and 3-indolebutyric acid (IBA) which have antioxidant and antifungal capacities are loaded on the chitosan nanosheet, and the chitosan-loaded benzene-containing carboxylic acid nanosheet is prepared. A derivative of the chitosan loaded alpha-naphthylacetic acid nanosheet and a derivative of the chitosan loaded 3-indolebutyric acid nanosheet are generated; the derivative can enhance the free radical scavenging capacity and antifungal activity of chitosan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nano materials, in particular to a chitosan-loaded benzene carboxylic acid-containing nanosheet. Background Art

[0002] With the development of science and technology, people's living standards are improving day by day, and research in the fields of medicine and food industry is particularly popular. Antioxidants and antifungals have always been difficult to overcome, and the research prospects are broad. In view of this, people's perspective on pharmaceutical engineering has also changed from disorder to orientation. Accurately preparing safe, efficient, low-toxic and good antioxidants and antifungals is the trend of research and development.

[0003] At present, there are few reports on the use of nano antifungal agents and antioxidants, and most of them use single substances to test the antifungal and antioxidant effects. Therefore, it is a new direction to develop new antifungal agents and antioxidants by simply modifying natural polymer compounds or preparing them into nano preparations, and conducting in-depth biological activity studies on them. Data show that the new nano antifungal agents and antioxidants developed are not only more effective than traditional antifungal agents and antioxidants, but also have fewer toxic and side effects and lower development costs.

[0004] Chitosan is a natural high molecular polymer with great potential, and nano-chitosan is a new type of carrier for effectively delivering functional groups and trace drugs, and has good biocompatibility and antifungal and antioxidant capabilities. Because its molecular structure contains active hydroxyl (-OH) and amino (-NH2), it can form derivatives with different structures and functions through various chemical modifications and modifications.

[0005] Some phenylcarboxylic acids have certain antioxidant and antifungal properties. However, the good lipid solubility of these phenylcarboxylic acids greatly limits their superior performance in organisms. Therefore, making full use of the biological activity of these substances while reducing their disadvantages can greatly improve their biocompatibility and practical application value. Summary of the invention

[0006] The purpose of the present invention is to provide a chitosan-loaded benzene carboxylic acid nanosheet. The present invention loads α-naphthylacetic acid (NAA) and 3-indolebutyric acid (IBA) with antioxidant and antifungal abilities onto the chitosan nanosheet to generate derivatives of the chitosan-loaded α-naphthylacetic acid nanosheet and derivatives of the chitosan-loaded 3-indolebutyric acid nanosheet; the derivatives can enhance the free radical scavenging ability and antifungal activity of the chitosan itself.

[0007] The present invention adopts the following technical solution:

[0008] The present invention provides a chitosan-loaded benzene carboxylic acid-containing nanosheet, and the preparation method is as follows:

[0009] Prepare low-temperature alkali-urea aqueous solution: dissolve alkali and urea in water to prepare the alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath.

[0010] Chitosan powder with a molecular weight of 20.0-30.0 kDa is dissolved in a low-temperature alkali-urea aqueous solution; a poor solvent is then added to precipitate chitosan nanosheets, and the solution changes from clear and transparent to a white turbid suspension; then, the suspension is centrifuged to separate solid chitosan nanosheets; the separated chitosan nanosheets are washed on a filter membrane with a poor solvent to remove alkali-urea.

[0011] The washed chitosan nanosheets are dispersed in a poor solvent; then, benzene carboxylic acid is added and stirred to dissolve, and the benzene carboxylic acid is α-naphthylacetic acid or 3-indolebutyric acid; then, evaporation and concentration are performed, and distilled water is added during the evaporation and concentration process; the solution is evaporated until it becomes viscous and hangs on the wall, and then taken out and freeze-dried to obtain chitosan-loaded benzene carboxylic acid nanosheets.

[0012] Furthermore, the alkali used in the alkali-urea aqueous solution is one or a mixture of NaOH, KOH, and LiOH.

[0013] Furthermore, the mass ratio of alkali to urea is 1:1.

[0014] Furthermore, the alkali-urea aqueous solution is precooled in an ice water bath to 0-24°C.

[0015] Furthermore, the alkali-urea aqueous solution is precooled to 0°C in an ice water bath.

[0016] Furthermore, the poor solvent is a mixture of one or more of alcohols, ketones, esters, furans, and pyridines.

[0017] Furthermore, a 0.22 μm filter membrane was used.

[0018] Further, the product was concentrated by evaporation using a rotary evaporator.

[0019] Furthermore, the freeze-drying temperature is -80°C, and the freeze-drying time is 24h.

[0020] The beneficial effects of the present invention are as follows: the present invention provides a chitosan-loaded benzene carboxylic acid nanosheet, wherein α-naphthylacetic acid (NAA) and 3-indolebutyric acid (IBA) having antioxidant and antifungal abilities are loaded onto the chitosan nanosheet to generate derivatives of the chitosan-loaded α-naphthylacetic acid nanosheet and derivatives of the chitosan-loaded 3-indolebutyric acid nanosheet; the derivatives can enhance the free radical scavenging ability and antifungal activity of the chitosan itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1This is a structural diagram of the chitosan-loaded α-naphthaleneacetic acid nanosheet derivative of the present invention.

[0022] Figure 2 This is a structural diagram of the chitosan-loaded 3-indolebutyric acid nanosheet derivative of the present invention.

[0023] Figure 3 This is the infrared spectrum of the chitosan nanosheets prepared in Example 1 of the present invention.

[0024] Figure 4 This is the infrared spectrum of the chitosan-loaded α-naphthylacetic acid nanosheets prepared in Example 1 of the present invention.

[0025] Figure 5 This is the infrared spectrum of the chitosan-loaded 3-indolebutyric acid nanosheets prepared in Example 4 of the present invention.

[0026] Figure 6 This is a scanning electron microscope image of the chitosan nanosheets prepared in Example 1 of the present invention.

[0027] Figure 7 This is a scanning electron microscope image of the chitosan-loaded α-naphthaleneacetic acid nanosheets prepared in Example 1 of the present invention.

[0028] Figure 8 This is a scanning electron microscope image of chitosan-loaded 3-indolebutyric acid nanosheets prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0029] In order to make those skilled in the art better understand the technical solution of the present invention, the present invention will be further described in detail in conjunction with specific embodiments. The following description is only used to illustrate the technical solution of the present invention but not to limit it. The experimental methods used in the embodiments are conventional methods unless otherwise specified. The materials and reagents used can be obtained from commercial sources unless otherwise specified. For example, chitosan (Mw = 20.0-30.0 kDa) in the present invention was purchased from Qingdao Yunzhou Biotechnology Co., Ltd., DD> 90%.

[0030] Example 1: A method for preparing chitosan-loaded α-naphthyl acetic acid nanosheets is as follows:

[0031] Prepare low-temperature alkali-urea aqueous solution: Take 15.0g NaOH and 15.0g urea and dissolve them in 300mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0032] Chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 5.0 g is dissolved in 300 mL of low-temperature alkali-urea aqueous solution, and stirred until the solution is transparent. The role of the low-temperature alkali-urea aqueous solution is to weaken the hydrogen bonds between chitosan molecules; the amount of the low-temperature alkali-urea aqueous solution is based on the reaction phenomenon, specifically, the chitosan is fully dissolved; then 500 mL of anhydrous ethanol (poor solvent) is added to precipitate chitosan nanosheets; the role of anhydrous ethanol is to change the polarity of the reaction system. When the amount of anhydrous ethanol input is greater than the amount of water input in the reaction system, the polarity of the reaction system changes; the reaction phenomenon is: the solution changes from clear and transparent to a white turbid suspension; then, the suspension is centrifuged to separate solid chitosan nanosheets; the separated chitosan nanosheets are repeatedly rinsed with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. The pH value of the filtrate is tested with a pH meter, and the pH value is between 7.0 and 8.0.

[0033] The washed chitosan nanosheets are dispersed in 500mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 5.0g of α-naphthylacetic acid is added and stirred for more than 8 hours; the reaction phenomenon is that α-naphthylacetic acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated and removed by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation, and the reaction phenomenon is that α-naphthylacetic acid is precipitated and attached to the surface of the chitosan nanosheet. The solution is rotary evaporated until it is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, i.e., chitosan-loaded α-naphthylacetic acid nanosheets.

[0034] Supplementary explanations are as follows: In the present invention, the alkali used in the alkali-urea aqueous solution can be selected from one or a mixture of NaOH, KOH, and LiOH. The relationship between the amount of alkali and the amount of urea is: the mass ratio of alkali to urea is 1:1; the mass ratio of water to the total amount of alkali and urea is 5:1; the relationship between the amount of alkali and the amount of chitosan is: the mass ratio of alkali to chitosan is 3:1. In addition, the optional temperature range of the low-temperature alkali-urea aqueous solution is 0-24°C; the lower the temperature, the smaller the hydrogen bonding effect between chitosan molecules. The present invention has found that 0°C is the optimal temperature for weakening hydrogen bonds.

[0035] Supplementary explanations are as follows: In the present invention, the poor solvent can be a mixture of one or more of alcohols, ketones, esters, furans, and pyridines. Among them, alcohols can specifically use anhydrous ethanol and methanol; ketones can specifically use acetone; esters can specifically use ethyl acetate; furans can specifically use tetrahydrofuran; pyridines can specifically use pyridine; the standard for the amount of poor solvent used to dissolve chitosan is: chitosan can be evenly dispersed in the solvent, and the reaction phenomenon is a white suspension.

[0036] Figure 3 This is the infrared spectrum of the chitosan nanosheet prepared in Example 1 of the present invention. Its characteristic infrared (cm -1 ): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900. Figure 3 It can be seen that the -1 The characteristic absorption peaks of OH and NH of chitosan nanosheets are located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is located at 1100-900cm -1 The absorption peak is the saturated -CH deformation vibration.

[0037] Figure 4 This is the infrared spectrum of chitosan-loaded α-naphthyl acetic acid nanosheets prepared in Example 1 of the present invention. Its characteristic infrared (cm -1 ): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900, 800-600. Figure 4 NAA-NMCS is located at 3600-3200cm -1 The characteristic absorption peaks of OH and NH of chitosan are located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is at 1100-900cm -1 The saturated -CH deformation vibration absorption peak is located at 800-600cm -1 The vibration absorption peak of the aromatic ring skeleton of the naphthalene ring appears at , proving that α-naphthaleneacetic acid is successfully loaded.

[0038] Figure 6 This is a scanning electron microscope image of the chitosan nanosheet prepared in Example 1 of the present invention. Its characteristic size is 500nm. Figure 6 It can be seen that nano-chitosan has a clear lamellar structure at a size of 500 nm, and the thickness of the lamellar structure is less than 50 nm.

[0039] Figure 7 This is a scanning electron microscope image of chitosan-loaded α-naphthyl acetic acid nanosheets prepared in Example 1 of the present invention. Its characteristic size is 500nm. Figure 7It can be seen that the surface of the nano-chitosan after loading α-naphthylacetic acid is obviously rough at a size of 500nm, but it still maintains a flaky structure, small molecular particles are attached to the gaps between the lamellae skeleton, and the lamellae thickness is less than 100nm.

[0040] Example 2: A method for preparing chitosan-loaded α-naphthylacetic acid nanosheets is as follows:

[0041] Prepare low-temperature alkali-urea aqueous solution: Take 5.0 g NaOH and 5.0 g urea and dissolve them in 100 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0042] Take chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 1.0 g and dissolve it in 100 mL of low-temperature alkali-urea aqueous solution, and stir until the solution is transparent; then add 200 mL of anhydrous ethanol (poor solvent) to precipitate chitosan nanosheets, and the solution changes from clear and transparent to a white turbid suspension; then, centrifuge to separate solid chitosan nanosheets; repeatedly rinse the separated chitosan nanosheets with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0 and 8.0.

[0043] The washed chitosan nanosheets are dispersed in 200mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 1.0g of α-naphthylacetic acid is added and stirred for more than 8 hours, and the reaction phenomenon is that α-naphthylacetic acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation process, and the reaction phenomenon is that α-naphthylacetic acid is precipitated and attached to the surface of the chitosan nanosheets. The solution is rotary evaporated until it is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, i.e., chitosan-loaded α-naphthylacetic acid nanosheets.

[0044] Example 3: A method for preparing chitosan-loaded α-naphthylacetic acid nanosheets is as follows:

[0045] Prepare low-temperature alkali-urea aqueous solution: Take 25.0 g NaOH and 25.0 g urea and dissolve them in 500 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0046] Take chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 10.0 g and dissolve it in 500 mL of low-temperature alkali-urea aqueous solution, and stir until the solution is transparent; then add 1000 mL of anhydrous ethanol (poor solvent) to precipitate chitosan nanosheets, and the solution changes from clear and transparent to white turbid suspension; then, centrifuge to separate solid chitosan nanosheets; repeatedly rinse the separated chitosan nanosheets with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0 and 8.0.

[0047] The washed chitosan nanosheets are dispersed in 1000mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 1.0g of α-naphthylacetic acid is added and stirred for more than 8 hours, and the reaction phenomenon is that α-naphthylacetic acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation process, and the reaction phenomenon is that α-naphthylacetic acid is precipitated and attached to the surface of the chitosan nanosheet. Rotary evaporation is performed until the solution is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, i.e., chitosan-loaded α-naphthylacetic acid nanosheets.

[0048] Example 4: A method for preparing chitosan-loaded 3-indolebutyric acid nanosheets is as follows:

[0049] Prepare low-temperature alkali-urea aqueous solution: Take 15.0g NaOH and 15.0g urea and dissolve them in 300mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0050] Take chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 5.0 g and dissolve it in 300 mL of alkali-urea aqueous solution, stir until the solution is transparent; then add 500 mL of anhydrous ethanol (poor solvent) to precipitate chitosan nanosheets, and the solution changes from clear and transparent to white turbid suspension; then, centrifuge to separate solid chitosan nanosheets; repeatedly rinse the separated chitosan nanosheets with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0 and 8.0.

[0051] The washed chitosan nanosheets are dispersed in 500mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 5.0g of 3-indolebutyric acid is added and stirred for more than 8 hours, and the reaction phenomenon is that 3-indolebutyric acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation process, and the reaction phenomenon is that 3-indolebutyric acid is precipitated and attached to the surface of the chitosan nanosheet. The solution is rotary evaporated until it is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, that is, chitosan loaded 3-indolebutyric acid nanosheets.

[0052] Figure 5 This is the infrared spectrum of chitosan-loaded 3-indolebutyric acid nanosheets prepared in Example 4 of the present invention. Its characteristic infrared (cm -1 ): 3600-3200, 3000-2800, 1750-1550, 1550-1450, 1100-900, 800-600. Figure 5 IBA-NMCS is located at 3600-3200cm -1 The characteristic absorption peaks of OH and NH of chitosan are broad and significantly enhanced, which is caused by the introduction of NH on the indole ring; located at 3000-2800cm -1 The saturated -CH stretching vibration absorption peak is located at 1750-1450cm -1 The characteristic absorption peak of -NH2 is at 1100-900cm -1 The saturated -CH deformation vibration absorption peak is located at 800-600cm -1 The aromatic ring skeleton vibration absorption peak of the indole ring appears at , proving that 3-indolebutyric acid is successfully loaded.

[0053] Figure 8 This is a scanning electron microscope image of chitosan-loaded 3-indolebutyric acid nanosheets prepared in Example 4 of the present invention. Its characteristic size is 500nm. Figure 8 It can be seen that the surface of the nano-chitosan after loading 3-indolebutyric acid is obviously rough at a size of 500nm, but it still maintains a flaky structure, with small molecular particles distributed throughout and wrapping the gaps between the lamellae, and the lamellae thickness is less than 100nm.

[0054] Example 5: A method for preparing chitosan-loaded 3-indolebutyric acid nanosheets is as follows:

[0055] Prepare low-temperature alkali-urea aqueous solution: Take 5.0 g NaOH and 5.0 g urea and dissolve them in 100 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0056] Take chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 1.0 g and dissolve it in 100 mL of alkali-urea aqueous solution, stir until the solution is transparent; then add 200 mL of anhydrous ethanol (poor solvent) to precipitate chitosan nanosheets, and the solution changes from clear and transparent to white turbid suspension; then, centrifuge to separate solid chitosan nanosheets; repeatedly rinse the separated chitosan nanosheets with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0 and 8.0.

[0057] The washed chitosan nanosheets are dispersed in 200mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 1.0g of 3-indolebutyric acid is added and stirred for more than 8 hours, and the reaction phenomenon is that 3-indolebutyric acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation process, and the reaction phenomenon is that 3-indolebutyric acid is precipitated and attached to the surface of the chitosan nanosheet. The solution is rotary evaporated until it is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, that is, chitosan loaded 3-indolebutyric acid nanosheets.

[0058] Example 6: A method for preparing chitosan-loaded 3-indolebutyric acid nanosheets is as follows:

[0059] Prepare low-temperature alkali-urea aqueous solution: Take 25.0 g NaOH and 25.0 g urea and dissolve them in 500 mL water to prepare alkali-urea aqueous solution, and precool the prepared alkali-urea aqueous solution in an ice water bath to reduce the system temperature to 0°C.

[0060] Take chitosan powder with a molecular weight of 20.0-30.0 kDa and a mass of 10.0 g and dissolve it in 500 mL of alkali-urea aqueous solution, and stir until the solution is transparent; then add 1000 mL of anhydrous ethanol (poor solvent) to precipitate chitosan nanosheets, and the solution changes from clear and transparent to white turbid suspension; then, centrifuge to separate solid chitosan nanosheets; repeatedly rinse the separated chitosan nanosheets with anhydrous ethanol (poor solvent) on a 0.22 μm filter membrane to remove alkali-urea. Use a pH meter to test the pH value of the filtrate, and the pH value is between 7.0 and 8.0.

[0061] The washed chitosan nanosheets are dispersed in 1000mL of anhydrous ethanol (poor solvent) and stirred until the solid is uniformly dispersed; then 1.0g of 3-indolebutyric acid is added and stirred for more than 8 hours, and the reaction phenomenon is that 3-indolebutyric acid is completely dissolved in anhydrous ethanol; the anhydrous ethanol in the system is separated by a rotary evaporator, and an appropriate amount of distilled water is added to the system during the rotary evaporation process, and the reaction phenomenon is that 3-indolebutyric acid is precipitated and attached to the surface of the chitosan nanosheet. The solution is rotary evaporated until it is viscous and hangs on the wall, and then it can be taken out for freeze drying to remove water. The freeze drying temperature is -80℃, and the freeze drying time is 24h (all water can be removed), and a white or off-white powder is obtained, that is, chitosan loaded 3-indolebutyric acid nanosheets.

[0062] The free radical scavenging test is as follows:

[0063] Hydroxyl radical scavenging ability: The ·OH in this test is generated by the EDTANa2-Fe(II)-H2O2 system. Safranin O can be uniquely locked by ·OH, causing it to fade. The content of ·OH can be measured by colorimetry based on the degree of fading. The specific test process is as follows:

[0064] ① Prepare phosphate buffer solution with pH = 7.4: Accurately weigh 5.2887g NaH2PO4·2H2O and 41.58g Na2HPO4·12H2O, add distilled water to make up to 1000mL, shake well, and store for later use.

[0065] ②Prepare Safranin O solution: Accurately weigh 36 mg of Safranin O, dissolve it in phosphate buffer solution, make up to 100 mL, shake well, and store for later use.

[0066] ③Prepare EDTA-Fe solution: accurately weigh 55.60 mg FeSO4 and 0.1489 g EDTA-Na2, mix and dissolve, dilute to 100 mL with distilled water, shake well, and store for later use.

[0067] ④Prepare 3% H2O2 solution: measure 5mL H2O2, use buffer solution as solvent, make up to 50mL, shake well, and store in dark place for later use.

[0068] ⑤ Accurately weigh 62.5 mg of L-ascorbic acid (Vc) and the sample to be tested (NMCS, NAA-NMCS, IBA-NMCS), and dilute to 25 mL with phosphate buffer solution. The reaction system is shown in Table 1 below.

[0069] Table 1

[0070] The blank group was added with 2.0 mL of water, and the control group was added with 2.0 mL of water and 4.0 mL of phosphate buffer solution (instead of H2O2), and the absorbance value A was measured at a wavelength of λ=600 nm.

[0071] Calculation formula:

[0072] Where, E—clearance capacity, %; A sample , A blank , A control —Absorbance value of sample, absorbance value of blank group, absorbance value of control group.

[0073] Superoxide anion scavenging ability: The superoxide anion (O2 - )The method of clearing ability is as follows.

[0074] ①Prepare Tris-HCl buffer solution: accurately weigh 1.9382g Tris and 0.8mL concentrated hydrochloric acid, mix, add water to make up to 1000mL, shake well, and store for later use.

[0075] ② Accurately weigh 36.57 mg NADH, 24.53 mg NBT, and 1.84 mg PMS respectively, prepare to 100 mL with buffer solution, and store for later use.

[0076] ③ Accurately weigh 62.5 mg of sample and prepare to 25 mL with buffer solution. The reaction system is shown in Table 2.

[0077] Table 2

[0078] The control group was added with 3.0 mL of Tris-HCl buffer solution, and the blank group was added with 4.0 mL of Tris-HCl buffer solution, 1.0 mL of NBT solution, and 1.0 mL of PMS solution. The absorbance value A was measured at a wavelength of λ=560 nm.

[0079] Calculation formula:

[0080] Where, E—clearance capacity, %; Asample, A control —Absorbance value of sample and control group.

[0081] DPPH free radical scavenging ability: Accurately weigh 7.1 mg DPPH and dissolve it in anhydrous ethanol, dilute to 500 mL, shake well, and save for later use. Prepare a sample solution of a certain concentration, and the reaction system is shown in Table 3.

[0082] Table 3

[0083] After measuring the absorbance value A1 at wavelength λ = 517 nm, 4.0 mL of anhydrous ethanol was added, and the absorbance value A2 was measured at wavelength λ = 517 nm. 4.0 mL of DPPH solution and 1.0 mL of distilled water were added to the blank group.

[0084] Calculation formula:

[0085] Wherein, E is the clearance capacity, %; A1, A2, A0 are the first absorbance value, the second absorbance value, and the absorbance value of the blank group.

[0086] Reducing ability: Prepare phosphate buffer solution: weigh 24.96g NaH2PO4·2H2O and 14.33g Na2HPO4·12H2O, add distilled water to 1000mL, shake well, and save for later use. Accurately weigh 62.5mg of the sample to be tested, and dilute to 25mL with phosphate buffer solution. The reaction system is shown in Table 4.

[0087] Table 4

[0088] The absorbance value A is measured at a wavelength of λ=700nm. The greater the absorbance, the stronger the reducing ability.

[0089] Antifungal tests are as follows:

[0090] Place the tested bacteria in a biosafety cabinet for activation, use an inoculation needle to intercept part of the colony on the slope, and inoculate it on the PDA medium. Check the growth of the bacteria after 3 days. If it is in a non-contaminated state, continue to culture. Preparation method of PDA medium: Peel 100g of potatoes, put them into 500mL of distilled water and boil for about 30 minutes. Then filter the potato solution, make up the required filtrate with distilled water, and add 15g of agar and 20g of glucose. After the mixture is packaged and sterilized, it is potato glucose agar (PDA) medium. Dissolve NMCS, NAA-NMCS, and IBA-NMCS in distilled water to prepare a starting concentration of 20mg·mL -1 The sample solution to be tested. Add a certain amount of the sample solution to the sterilized PDA medium, shake well, prepare the medium with drug content of 2.0mg / mL, 1.0mg / mL, 0.5mg / mL, 0.25mg / mL, 0.125mg / mL, and 0.0625mg / mL, and pour it into a culture dish (9cm in diameter). Three parallel experiments were performed for each sample. Using distilled water as the negative control, inoculate fungal plugs (5mm) on each culture dish. After culturing at 28°C for 48h, measure the colony diameter, and calculate the antibacterial rate according to the following formula:

[0091] E(%)=(Φ a-Φ b / Φ a -5)×100%.

[0092] Among them, Φ a is the mycelial growth diameter of the negative control medium, Φ b is the diameter of mycelial growth in the sample culture medium.

[0093] The free radical scavenging test results are analyzed as follows:

[0094] Table 5 below is a statistical table of free radical scavenging test results of the chitosan nanosheets of the present invention.

[0095] Table 5

[0096] As can be seen from Table 5, chitosan nanosheets have a certain ability to scavenge free radicals. The scavenging and reducing abilities of chitosan nanosheets for hydroxyl radicals, superoxide anions, and DPPH radicals all increase with increasing concentrations. At a concentration of 0.5 mg / mL, the scavenging rates of hydroxyl radicals, superoxide anions, and DPPH radicals were 31.54%, 19.35%, and 59.96%, respectively, and the reducing ability was 0.017 Abs.

[0097] Table 6 below is a statistical table of free radical scavenging test results of chitosan-loaded α-naphthylacetic acid nanosheets of the present invention.

[0098] Table 6

[0099] As can be seen from Table 6, NAA-NMCS has good DPPH free radical scavenging and reducing abilities, especially the reducing ability, which is as high as 0.036Abs at a concentration of 0.5mg / mL, exceeding NMCS by 0.019Abs. This indicates that chitosan-loaded α-naphthyl acetic acid nanosheets have a certain in vitro antioxidant capacity.

[0100] Table 7 below is a statistical table of free radical scavenging test results of chitosan-loaded 3-indolebutyric acid nanosheets of the present invention.

[0101] Table 7

[0102] As can be seen in Table 7, IBA-NMCS has good free radical scavenging and reducing abilities, and the overall levels are higher than NMCS. At a concentration of 0.5 mg / mL, the hydroxyl radical scavenging rate was 46.43%, 14.89% higher than NMCS; the superoxide anion scavenging rate was 21.35%, 2.00% higher than NMCS; the DPPH radical scavenging rate was 84.06%, 24.10% higher than NMCS; the reducing ability was 0.113 Abs, 0.096 Abs higher than NMCS. This shows that chitosan-loaded 3-indolebutyric acid nanosheets have good in vitro antioxidant ability in vitro.

[0103] The antifungal test results are analyzed as follows:

[0104] Table 8 below is a statistical table of fungus inhibition test results of the chitosan nanosheets of the present invention.

[0105] It can be seen from Table 8 that chitosan nanosheets have certain antifungal ability. The inhibition rate of NMCS against wheat Gibberella is 15.37%, the inhibition rate of wheat rhizoctonia is 39.31%, the inhibition rate of tomato early phytophthora is 41.18%, the inhibition rate of pepper phytophthora is 34.35%, the inhibition rate of sweet potato phytophthora is 46.92%, and the inhibition rate of Botrytis cinerea is 92.98%.

[0106] Table 9 below is a statistical table of fungus inhibition test results of the chitosan-loaded α-naphthaleneacetic acid nanosheets of the present invention.

[0107] Table 9

[0108] As can be seen from Table 9, the antibacterial rate of chitosan-loaded α-naphthaleneacetic acid nanosheets increases with the increase of concentration, showing a good linear relationship. It has a strong inhibitory ability against wheat fusarium, wheat leaf blight, pepper phytophthora, sweet potato phytophthora and gray botrytis. At a concentration of 2.0 mg / mL, the inhibition rate can reach 100.00%, and the inhibition rate against tomato early phytophthora can also reach 95.47%. Chitosan-loaded α-naphthaleneacetic acid nanosheets have excellent antifungal properties and are ideal plant antifungal agents.

[0109] Table 10 below is a statistical table of fungal inhibition test results of the chitosan-loaded 3-indolebutyric acid nanosheets of the present invention.

[0110] Table 10

[0111] As can be seen from Table 10, the antibacterial rate of chitosan-loaded 3-indolebutyric acid nanosheets increases with the increase of concentration, showing a good linear relationship. It has a strong inhibitory ability against wheat fusarium, wheat leaf blight, pepper phytophthora, sweet potato phytophthora and gray botrytis. At a concentration of 2.0 mg / mL, the inhibition rate can reach 100.00%, and the inhibition rate against tomato early phytophthora can also reach 95.53%. Chitosan-loaded 3-indolebutyric acid nanosheets have excellent antifungal properties and are ideal plant antifungal agents.

[0112] The above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation methods. For those of ordinary skill in the art, other different forms of changes can be made based on the above description. And the obvious changes derived from this belong to the scope of protection of the present invention. Finally, it should be noted that the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

Claims

1. A chitosan-loaded phenylcarboxylic acid nanosheet, characterized in that: The preparation method is as follows: Preparing a low-temperature alkali-urea aqueous solution: dissolving alkali and urea in water to prepare an alkali-urea aqueous solution, and precooling the prepared alkali-urea aqueous solution in an ice water bath; Chitosan powder with a molecular weight of 20.0-30.0 kDa is dissolved in a low-temperature alkali-urea aqueous solution; a poor solvent is then added to precipitate chitosan nanosheets, and the solution changes from clear and transparent to a white turbid suspension; then, the suspension is centrifuged to separate solid chitosan nanosheets; the separated chitosan nanosheets are washed on a filter membrane with a poor solvent to remove alkali-urea; The washed chitosan nanosheets are dispersed in a poor solvent; then, benzene carboxylic acid is added and stirred to dissolve, and the benzene carboxylic acid is α-naphthylacetic acid or 3-indolebutyric acid; then, evaporation and concentration are performed, and distilled water is added during the evaporation and concentration process; the solution is evaporated until it becomes viscous and hangs on the wall, and then taken out and freeze-dried to obtain chitosan-loaded benzene carboxylic acid nanosheets.

2. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: The alkali used in the alkali-urea aqueous solution is one of NaOH, KOH, LiOH or a mixture of multiple thereof.

3. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: The mass ratio of alkali to urea is 1:

1.

4. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: The alkali-urea aqueous solution was precooled in an ice water bath to 0-24°C.

5. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 4, characterized in that: The alkali-urea aqueous solution was precooled to 0°C in an ice water bath.

6. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: The poor solvent is a mixture of one or more of alcohols, ketones, esters, furans and pyridines.

7. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: A 0.22 μm filter membrane was used.

8. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: Concentrate by evaporation on a rotary evaporator.

9. The chitosan-loaded phenylcarboxylic acid-containing nanosheet according to claim 1, characterized in that: The freeze-drying temperature was -80°C and the freeze-drying time was 24h.